Development of a Segmental Long-bone Defect Model in Sheep - Mathon, D. H.; Frayssinet, P.; Asimus, E.; Chanoit, G.; Collard, P.; Autefage, A. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
A 10 mm-long (Group #1) or 20 mmlong (Group #2) segmental osteoperiosteal defect was performed on the metatarsus of ten adult ewes (5+5). The goal of the study was to search for a critical size defect model leading to nonunion. The bone gap was maintained for three months with an internal fixation device involving two plates set in orthogonal planes. Radiological and histological examinations were performed on harvested metatarsal bones. Three months after surgery Group #1 animals showed obvious signs of bone healing without achieving complete union in all cases. Evidence of a healing process was not observed in Group #2 animals, and histological examination confirmed the complete failure of bone repair in the 20 mm gaps. These results are comparable to those of other authors who have concluded that a bone gap corresponding to 1.4 times the diaphyseal diameter overshoots physiological bone healing capacities. This long bone defect model showed good biological properties allowing callus settlement with minimal impairment in Group #1 and permitted weightbearing and unrestricted motion in the animals. Such a sheep model would be useful for testing hard tissue biomaterials, bone healing enhancement or further developed as an experimental nonunion model.Metatarsal diaphyseal defects (length: 10 or 20 mm) maintained with plates were performed in sheep in search of nonunion after a three-month period. Radiological and histological examinations showed that 10 mm gaps healed spontaneously while 20 mm gaps did not. These results are comparable to those of other authors who concluded that a diaphyseal defect whose length exceeds 1.4 times its diameter is unable to repair. The good biological properties exhibited by this defect model seem to be convenient for testing bone substitutes or bone healing enhancement techniques.
Keywords: Bone defect; nonunion; sheep; metatarsus; bone substitute